ANALYSIS OF IMPORTANT, CAREFUL, CERTAIN AND MUTUALLY AGREEABLE CRITERIA IN THE REGULATION OF ARTICLE 173 OF THE HERZIEN INLANDSCH REGLEMENT REGARDING EVIDENCE OF JUDGES' SUSPECTS - Naufal Anfasa Firdaus; Yenny Eta Widyanti; Rachmi Sulistyarini (CV. RADJA PUBLIKA, 2025)
The sentence in Article 173 HIR which states